„…testament zapisany na zdjęciu: oto tak wszystko powinno wyglądać”: fotografia między narracją o katastrofie a katastrofą narracji – na przykładzie opowiadania Savyon Liebrecht „Album mamy” - Szczypiorska-Chrzanowska, Magdalena (Załącznik Kulturoznawczy, 2024)
“To explain the Holocaust, new ways of defining things should be invented, because the criteria we use to evaluate events in normal circumstances cannot be applied to survivors” – writes Savyon Liebrecht, a representative of the second generation, in her introductory note to the selection of short novels Excision. The short story Mother’s Photo Album from the Excision collection points to the entire inventory of strategies how (not) to talk about Holocaust, setting in the center of the events the photo album, understood as a construct shaping the biographies of the characters in the form of idealized, wishful reality, on the periphery of what is most traumatic, painful, impossible to accept. The smooth surface of the photographic print obscures, hides, replaces images retained in the memory of the child born to a couple of survivors creating the world as “it should be” in opposition to the real world. The game of tensions between the biography and its supposedly photographic representation, the photo album, reveals multi-level relations between the imposing silence of the language and the hurly-burly of the photography, between the ethical understatement and the aesthetic excess, between a narrative of the disaster and a narrative disaster.